No Detection of Crimean Congo Hemorrhagic Fever (CCHF) Virus in Ticks from Kerman Province of Iran - Sahar Khakifirouz; Seyed Javad Mowla; Vahid Baniasadi; Mehdi Fazlalipour; Tahmineh Jalali; Seyedeh Maryam Mirghiasi; Mostafa Salehi-Vaziri (Pasteur Institute of Iran, 2018)
Introduction: Crimean Congo Hemorrhagic Fever (CCHF) is a fatal tick-borne viral zoonosis with a case fatality rate of 5% to 30%. CCHF has been documented as the most frequent tick-borne viral infection in Iran with more than 50 cases annually. Kerman Province in the south of Iran is one of the CCHF-endemic areas of the country, but no data on infection of ticks with this virus from this area is available. This study aimed to investigate the CCHFV infection among ticks collected from 4 different counties in this province. Methods: In 2011, a total of 203 hard ticks were collected from Kerman, Jiroft, Sirjan, and Kuhbanan counties in Kerman Province, southeast of Iran. Infection of ticks with CCHFV was investigated using RT-PCR targeting the small segment of the viral genome. Results: Out of 203 ticks, Dermacentor (50.24%) was the most frequent genus followed by Hyalomma (39.39%), Haemaphysalis (9.85%) and Rhipicephalus (0.49%). Our results showed no CCHFV infection of ticks. Conclusion: Our finding indicates no circulation of CCHFV in ticks from Kerman Province. However, as Kerman Province is an endemic region for CCHF, further investigations are needed to have a better understanding of the CCHFV vectors in this region.